Theory and practice of soil loss control in Eastern China - Zhang, J.C (Springer, 2011)
In recent decades in eastern China there has been great progress towards ecological restoration through reforestation of bare lands and steeply sloping cultivated land suffering from serious erosion. This book introduces several soil loss control models suitable for land use strategies along with many techniques of reforestation with a focus on improving the living standards of farmers. These strategies include local recycling, which combines the use of trees (fruit trees, herb, bamboo), crops for feeding livestock, use of animal wastes for biogas and fertilizer, fish production, and a large scale recycling, fostering the interaction between the countryside of the mountainous areas and the urban areas in the lower elevations. The local recycling can alleviate poverty for farmers and provide fuel material that replaces dependence on twigs and tree litter, which in turn protects the reforested young trees from being harmed. The large scale recycling creates a more harmonious society and promotes the common health and wealth of the countryside and the city. This book presents the most comprehensive and successful models of reforestation in eastern China.